Contratos atípicos e innominados - Sidney Alex Bravo Melgar
Franchising. Know how. El factoring. Underwriting. Joint venture.leasing. Fideicomiso. Swap.renting. engineering. Countertrade. Barter. Concesión. Distribución. Management. Corretaje. Sponsorship. Credit card. Merchandising. Commodities. Compraventa internacional. Consulting. Agency. Contratos informáticos. Securitizacion. Contratos electrónicos. Outsourcing.